THE GENE CLONING, OVEREXPRESSION, PURIFICATION, AND CHARACTERIZATION OF DIBENZOTHIOPHENE MONOOXYGENASE AND DESULFINASE FROM GORDONIA ALKANIVORANS RIPI90A - Mahmoud Shavandi; Majid Soheili; Shokufeh Zareian; Neda Akbari; Khosro Khajeh (Journal of Petroleum Science and Technology, 2013)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-language: AR-SA; mso-ansi-language: EN-US; mso-fareast-language: EN-US;">The biodesulfurization (BDS) of sulfur compounds in fossil fuels is a process to reduce sulfur dioxide emissions that cause environmental pollution. Gordonia alkanivorans RIPI90A is able to convert dibenzothiophene, an organic sulfur compound in petroleum, to 2-hydroxybiphenyl (2-HBP) in 4S pathway. In this study, (DBT), DszA and DszB, DBT sulfone monooxygenase, and desulfinase were respectively isolated from G. alkanivorans RIPI90A. PCR amplified fragments were obtained by using primers designed based on known sequences from G. alkanivorans RIPI90A. They are identified as dszA and dszB and have shown high similarity compared to Rhodococcus erythropolis IGTS8 (88% for dszA and 88% for dszB). Subsequently, dszA and dszB genes were expressed under the control of T7 promoter in Escherichia coli. The recombinant proteins were purified to achieve homogeneity using Ni-agarose column chromatography. The molecular mass of the purified DszA and DszB were determined to be 51.9 and 39.2 kDa respectively by using SDS-polyacrylamide gel electrophoresis. DszA showed a Km of 0.14±0.005 mM and a maximal velocity of 0.004±0.0004 mM/min. DszB showed a wide substrate range in a way that all aromatic sulfonates compounds acted as its substrate; as it seemed the active site was suitable for the sulfonated aromatic rings. The Km and Vmax values of DszB were calculated to be 1.81±0.02 mM and 6.55 ± 0.005 µM/min respectively using 4-Amino-3-hydroxy-naphthalene-sulfonic acid as a substrate